Multimedia communications, services and security : 9th International Conference, MCSS 2017, Kraków, Poland, November 16-17, 2017, proceedings /: 9th International Conference, MCSS 2017, Kraków, Poland, November 16-17, 2017, proceedings. (2017) - Unknown
No abstract available